(3fJGFL GdCPcGQ aj GdbQHjf hGdCHQGQs - (3eMeO Hf Ydj Hf eMeO Hf YQHj , CHh HcQ GdMGJej GdWGFj GdCfOdSj, GdeYQha HeMjj GdOjf GHf YQHj,J (B638 (3g` s ((3eMeO Hf YHO GdhgGH Hf CMeO Hf eMeO Gdejei s)
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf PcQ SHMGf GdOGFe GdbGFe SHMGf GdbGFe GdOGFe jfJL ai GdebQH jOhe djbhe hjbhe djOhe eLedkG HYO age UMjM s
(3BNQgG (B:s
(3PcQ dG Edg EdG Gddg Gdedc GdMb GdeHjf gPG GdPcQ jfHZi Cf jSJYedg GdEfSGf HYO aQGZg eeG jbhd ai hbJ Cf jbhd hGddg jbhd GdMb hgh jgOi GdSHjd Je hGdMeO ddg QH GdYGdejf s
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B281 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B40s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1924s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs